Omega 3/omega 6 balanced safflower-flaxseed co-pressing oil: quality attributes and flavor profile characterization - Ruonan He; Huixin Luo; Yu’e Ma; Honghong Zhang; Lingdong Zhao; Jianing Liu; Wenhao Li; Changqing Wei; Yi Zhao; Peng Luo (Food Research International, 2026)

Complex evolutionary history of Rosales mediated by extensive incomplete lineage sorting and hybridization - Luxian Liu; Weiwei Lv; Douglas E. Soltis; Hans Peter Comes; Yonghua Zhang; Yu Shi; Shufen Li; Meizhen Wang; Wujun Gao; Pan Li (Molecular Phylogenetics and Evolution, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

Microplastic sedimentary records in a shallow lake of North China: Identifiable responses to hydrological and socio-economic drivers - Yutao Zuo; Yawen Ge; Xin Mao; Yuhang Xia; Xinjie Li; Changhong Liu; Huiyuan Jia; Yuecong Li; Ke Zhang; Michael E. Meadows (Water Research, 2026)

Embedding bio-Fenton in a hybrid membrane biofilm reactor enhances the treatment of antibiotic-contaminated saline water - Wei Li; Ying-Lian Lan; Xu Zhang; Yi-Hao Luo; Yu-Xiang Zhao; Ju-Ying Lei; Yong-Di Liu; Bruce E. Rittmann (Water Research, 2026)

An integrated multiscale air quality modelling framework for industrial park pollution: Linking local emissions to regional transport - Tao Wang; Jie Li; Joshua S. Fu; Wei Wang; Bing Liu; Bin Zhao; Yibo Zhang; Jinxiu Pan; Feng Sun; Xiu’e Shen; Zhe Wang; Xiao Tang; et al. (Journal of Environmental Sciences, 2026)

Maize attainable yields across China reveal unrealized potential for sustainable food security - Jingjing Wang; Zhijuan Liu; Zhenkang Yang; E Li; Jiangjiang Xia; Jingjin Gong; Huihui Qu; Tao Li; Xiaomao Lin; Xiaoguang Yang (Field Crops Research, 2026)

Residues, drivers, and health implications of herbicides in typical black soil regions of China: Soil-crop system linkage and targeted human risk - Le Jian; Hanqiang Liu; Wenyou Hu; Peter E. Holm; Rui Li; Wenxue Niu; Feng Liu; Yuguo Zhao; Yongcun Zhao; Biao Huang (Environmental Pollution, 2026)

Distinct ages and mantle sources for Southern Ocean oceanic plateaus - Peter C. Davidson; Jörg Geldmacher; Yuji Ichiyama; Jia Liu; Folkmar Hauff; Anthony A.P. Koppers; Daniel E. Heaton; Daniel A. Frick; Kaj Hoernle; Odysseas A. Archontikis; Sietske J. Batenburg; Peter Bijl; et al. (Earth and Planetary Science Letters, 2026)

Cyclodextrin-engineered bioinspired nanozyme microneedle for adaptive theranostic regulation of hyperuricemia and gout - Xu-Wei Qi; Hua-Zhou Niu; Ya-Hui Chen; Ye-Tao Zhang; Jing Li; Zu-E Hu; Jia-Xin Wang; Yi-Qi Liu; Bang-Jing Li; Sheng Zhang (Carbohydrate Polymers, 2026)

Salmonella risk prediction in poultry farms via deep learning image classification Models, Cross-Region Validation, and edge computing - Venkat Umesh Chandra Bodempudi; Guoming Li; Adelumola Oladeinde; Michael J. Rothrock; Samuel E Aggrey; Tongshuai Liu; Sai Akshitha Reddy Kota; Geng Yuan; Sravan Sai Rahul Nalla (Computers and Electronics in Agriculture, 2026)

Unraveling the Co-release Dynamics of Micro/nanoplastics and Toxic Transformation Products from Weathered Single-Use Plastics - Guoxin Li; Ziyi Liu; Yongrong Hu; E Xiang; Shangsi Lv; Shuofei Dong; Dong Yan; Yuxiong Huang (Water Research, 2026)

Zn-La staged modification of reed biochar for adsorption of tetracycline hydrochloride and mechanism study - Zhengqi Liang; Xiongyan Gao; Yushan Li; Xu Liu; Boxing An; Yingying Zuo; Ling Wang; Jiahui Fu; Meili E (Journal of Water Process Engineering, 2026)

Allochthonous particulate organic carbon in blue carbon ecosystems: Implications for accounting, stability, and policy - Anirban Akhand; Inés Mazarrasa; Stacey M. Trevathan-Tackett; K.M.G. Mostofa; Abhra Chanda; Hongbin Liu; Hiroshi Sakugawa; Si-Liang Li; Cong-Qiang Liu; Catherine E. Lovelock; Paul Lavery; Hilary Kennedy; et al. (Journal of Environmental Management, 2026)

Bioaugmentation of Rhodococcus ruber F1 achieved simultaneous removals of benzophenone-3 and ammonium - Fei Liu; Chenyu Li; Yuxuan Zhou; Mo Li; Zhicheng Pan; Fu Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2026)

Enhancing reproducibility in neuroimaging with containerized archival - Michael E. Kim; Praitayini Kanakaraj; Yihao Liu; Trent Schwartz; Zhiyuan Li; Nancy R. Newlin; Chenyu Gao; Kurt G. Schilling; Shunxing Bao; Baxter P. Rogers; Bennett A. Landman; Karthik Ramadass (Brain Imaging and Behavior, 2026)
Ensuring reproducibility in scientific research is crucial for validating findings, advancing knowledge, and fostering trust within the scientific community. Containerization of code is a widespread practice to help ensure reproducibility in neuroimaging research. However, there exists no universal method of sharing containers, nor is it feasible to broadly enforce rules due to the diversity of research practices. We posit that container sharing should include 1.) public availability, 2.) self-contained documentation, and 3.) procedures to ensure consistency of the container and its expected outputs. We demonstrate an approach for publicly releasing three separate containers using Zenodo. Our proposed method fulfills the design criteria for container sharing while incurring minimal overhead. As there are several tools available to distribute and maintain containers already, we discuss available alternatives.

Cold seep environment shapes the structure and metabolic potential of mesopelagic fish gut microbiota - Xiyue Yang; Chunhou Li; Yong Liu; Zuozhi Chen; Yan′e Jiang; Min Li; Yancong Cai; Jian Zou; Shannan Xu; Yayuan Xiao; Yu Liu; Dajuan Zhang; et al. (Regional Studies in Marine Science, 2026)

Integrative genomic analyses reveal genetic structuring and cyto-nuclear incongruences within the Corbicula species complex in China - Yangxin Tang; Linwei Liu; Jie Pi; Xinhua Liu; Jianguo Xiang; Joong-Ki Park; Neil E. Coughlan; Deliang Li (Molecular Phylogenetics and Evolution, 2026)

Pore structure evolution in organic-rich shale during thermal maturation: Insights from hydrous pyrolysis of two lacustrine kerogens - Fengtian Bai; Lee A. Stevens; Clement N. Uguna; Wei Li; Will Meredith; Colin E. Snape; Christopher H. Vane; Yumin Liu; Chenggong Sun (Fuel, 2026)

MgI2 immobilized nitrogen and phosphorus co-doped hollow carbon cubes as a multifunctional host for high-performance lithium‑sulfur batteries - Sheng Liang; Cong Li; Zi-Hao Chen; Lei Hu; Xin Liang; Ling-Li Liu; Li-Li Wang; Ning-Ning Zhou; Bin Chen; Wen-Yu Gu; San-E Zhu (Chemical Engineering Journal, 2026)

Metallogenic Mechanism for the Deep Part of the Jiaojia Gold Zone in the Eastern North China Craton (Jiaodong): Constrains from Pyrite Re-Os Geochronology, in-situ Trace Elements and Sulfur Isotope Compositions - Naijie Chi; Zuozhen Han; Xuefeng Yu; Wei Shan; Chuan’e Liu; Xiufeng Wang; Zengsheng Li; Shenghu Li; Chenxi Zhang; Xiangxian Ma (Journal of Earth Science, 2026)

Discovery of novel cinnamic acid derivatives with anti-Helicobacter pylori mechanism - Yonglian Li; Xiuya Ye; Yuan’e Yang; Wenfeng Liu; Suqing Zhao (Molecular Diversity, 2026)

The role of ecosystem conservation and restoration in achieving the SDGs - Yizhong Huan; Guangjin Zhou; Alice C. Hughes; Xiaoyun Li; Peng Hou; Marco Lambertini; Tao Liang; Wenwu Zhao; Binoy Sarkar; Alexandre Betinardi Strapasson; Yiming Su; Xiaoman Liu; et al. (Science Bulletin, 2026)

A field-scale model using an integrated framework for evaluating food and water dynamics in agrivoltaics in three-dimensional space - Anh H. Nguyen; Yaoze Liu; Siyu Li; Zhuohang Wu; Majdi R. Abou Najm; Liming Zhou; Xiaobo Xue Romeiko; Richard R. Perez; Mark E. Uchanski; Jennifer M. Bousselot; Hu Liu; Chuandong Wu (Journal of Cleaner Production, 2026)

Triplex-helix molecular beacon-enabled CRISPR/Cas12a biosensor for sensitive detection of SARS-CoV-2 - Yuesheng Wang; Shuying Zhang; Jingyu Chen; Ge Qin; Qiongwen Zhang; Yuxi Liu; Dan Yue; Fanting Wang; Shan Wei; Di Wu; Wenqiao Zang; Li-e Liu; et al. (Chemical Engineering Journal, 2026)

Transcriptomic and proteomic insights into the molecular mechanism underlying cell wall biosynthesis in Moso bamboo (Phyllostachys edulis) - Xin Geng; Yilan E; Xiaojing Wang; Yanjing Liu; Bowen Li; Qingyu Jin; Yuzhen Chen; Cunfu Lu (Plant Cell Reports, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Coupling effect of urban building clusters and crosswinds on the aerodynamic performance of high-speed maglev trains - Jianfeng Mao; Xi Wang; Yikang Liu; Zhiwu Yu; Zheng Li; E Deng (Sustainable Cities and Society, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Quantitative microbiological risk assessment of Shiga toxin-producing Escherichia coli contamination for the beef steak supply chain in China - Xueqing Jiang; Yimin Zhang; George-John E. Nychas; Lixian Zhu; Yunge Liu; Rongrong Liang; Xiaoyin Yang; Ke Li; Pengcheng Dong (International Journal of Food Microbiology, 2026)

W/O/W emulsion-filled egg white gel co-stabilized by protein and γ-cyclodextrin MOFs with multi-chamber encapsulation potential - Chan Li; Xue Yang; Yunfei Zou; Li Zhang; Chuhuan Wei; Yan Ran; E Zhao; Jibiao Yuan; Keshan Wang; Yongguo Jin; Ying Zhou; Qiujin Zhu; et al. (Food Research International, 2026)

Biomagnification of persistent organic pollutants from diets and microplastics to a seabird species (Sula sula) - Ruifeng Lu; Xiaobo Zheng; Lei Li; Yiye Jiang; Jian Guo; Yin-E Liu; Bixian Mai (Environmental Pollution, 2026)

“Global significant trends and countermeasures pertaining to climate change adaptation: Translating ambition into action post-COP29” - Shuo Liu; Yu-E. Li; Qin Ouyang (Environmental Science & Policy, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Integrating crowdsourced geospatial intelligence and urban morphology for urban waterlogging risk mapping in Karachi, Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Chengshuai Liu; Junaid Abdul Wahid; Jiali Guo; Xiaotao Shi; Gul-e-Zehra Soomro (Climatic Change, 2026)

The occurrence of extreme heat events offset CO2 fertilization and deteriorate grain quality in double cropping rice systems under projected climate change - Huan Liu; Bin Wang; Yu’e Li; Lu Sun; Longlong Xia; Kees Jan van Groenigen; Yunfan Wan; Tiantian Miao; Weilu Wang; Diego Abalos; Lewis H. Ziska (Agricultural and Forest Meteorology, 2026)

The naked mole-rat cGAS promotes homologous recombination repair and delays aging - Chenxi Du; Yuying Xie; Haolin Ding; Taoxia E; Linpeng Li; Xingguo Liu (Science Bulletin, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

Tris(2,4-di-tert-butylphenyl) phosphate induces cardiac injury in juvenile mice by disrupting energy homeostasis: Focus on mitochondrial impairment - Xiangxiang Chen; Yanan Xia; Lihua Feng; Haoneng Li; Yang'e Li; Shixiang Huang; Hengyi Xu; Yang Liu (Chemico-Biological Interactions, 2026)

The hydroxyl content of biochar mediates the coating structure to dominate the release performance of castor oil-based polyurethane coated urea - Zexi Li; Yufeng Chen; Ruhong Qin; Qianqian Dai; Chunxia Ding; A-juan Zhao; Xiangrong Liu; Fangfang Wu; Mei-e Zhong (Environmental Research, 2026)

Joint Influence of Seed Dormancy and Dispersal Syndrome on Dispersal Distance and Range Size Across Two Climate Regions - Wang Cai; Yuan Liu; YunAo Li; Min Cao; Carol C. Baskin; Jerry M. Baskin; Adriana Alzate; Renske E. Onstein; Jie Yang (Global Ecology and Biogeography, 2026)
Aim Long distance dispersal and the ability to delay germination under unfavourable conditions (dormancy) are critical for plant persistence and range expansion. However, how dispersal syndrome and dormancy interactively shape maximum dispersal distance and species range size across climate regions remains unclear. We tested the hypothesis that a trade‐off between dormancy and dispersal distance operates differently in animal‐mediated versus abiotic dispersal systems, and that climate modulates their influence on range size. Location Global. Time Period Current. Major Taxa Studied Seed plants. Methods We compiled data on dormancy, dispersal syndrome, maximum seed dispersal distance and range size for 631 plant species across 118 families worldwide. We used linear mixed effects models to examine how dormancy and dispersal syndromes interactively shape seed dispersal distance and range size across tropical and temperate regions. Results Non‐dormant species had larger maximum dispersal distances than dormant species, but only in abiotic dispersal systems, consistent with a trade‐off between dispersal and persistence traits (dormancy). In contrast, animal‐mediated dispersal led to larger dispersal distances than abiotic dispersal, regardless of whether species were dormant or not. The influence of dormancy and dispersal syndrome on range size was climate‐dependent. In tropical regions, animal‐mediated dispersal enhanced range size, while dormancy had little effect. In temperate regions, maximum seed dispersal distance was positively associated with range size, but neither dormancy nor animal‐mediated dispersal significantly affected range size. Main Conclusions The interplay between seed dormancy and dispersal syndromes shapes seed dispersal distance and species range size in climate‐specific ways. Animal‐mediated dispersal promotes larger maximum dispersal distances and larger range sizes in tropical regions. In contrast, in abiotic dispersal systems, dormancy leads to relatively small dispersal distances, but dormancy itself does not affect range sizes in temperate or tropical regions. Understanding dispersal‐dormancy dynamics is essential for predicting how plants will respond to environmental changes.

Priorities for enhancing resilience of SDG causal network from a human-nature perspective - Yiming Su; Guangjin Zhou; Mingyuan Wang; Xiaoyun Li; Tao Liang; Lingqing Wang; Jian Hu; Jixi Gao; Wenwu Zhao; Siyuan Tao; Peter E. Holm; Jörg Rinklebe; et al. (Resources, Conservation and Recycling, 2026)

A new method for planning long-distance trails using wilderness quality mapping and trajectory data: A case study of the Taihang Mountain National Forest Trail in China - Yunmiao Chen; Yue Cao; Zhangqian Ye; Tao Liu; Pei Wang; Yunshuang Feng; Lingyun Liao; Mingyang Lv; Zhicong Zhao; Alan E. Watson; Steve Carver; Changjia Li; et al. (Journal of Environmental Management, 2026)

Establishment of an efficient cotyledon-based regeneration system in Juglans sigillata dode - Xiaojin Liu; Chunxiang Li; Wenlong Zhang; Jian Peng; Xuejun Pan; Wen’e Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Synergistic importance of memory and spatial neighbourhood effects in modelling net ecosystem productivity - Jian Liu; Tao Zhou; Jingyu Zeng; Jingzhou Zhang; Xuemei Wu; Yajie Zhang; Qi Zhang; Yancheng Qu; Peixia Liu; Wenjuan Zhang; E Tan; Ying Yu; et al. (Agricultural and Forest Meteorology, 2026)

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

Shifts in microorganisms lead to double peaks in manure-induced temperature sensitivity of soil organic carbon degradation with incubation time - Xiaodong Sun; Yikang Xue; Yu'e Li; Kailou Liu; Wenju Zhang; Minggang Xu; Andong Cai (Soil and Tillage Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Nonnegligible migration of rubber-derived chemicals from road surface to adjacent greenbelt soil - Zhen-Yu Ge; Hai-Yan Zhang; Xue-E Li; Yue-Hong Liu; Li-Ni Wei; Xiang-Ning Liang; Yan-Feng Lv; Tuan-Tuan Wang; Sai Wang; Jian-Liang Zhao (Journal of Hazardous Materials, 2026)

Deep eutectic solvents-synergistic ultrasonic-assisted extraction of polyphenols from flaxseed (Linum usitatissimum L.) meal: Optimization, mechanisms, in vitro activity, and structural characterization - Zhanglian Chen; Shiyong Li; Zhilin Zhou; Jiaqi Zhao; Yuxin Fu; Xiaoman Qin; E-yu Ma; Xinyi Jiang; Wenyu Liu; Hongbin Wu; Yi Xu; Changqing Wei (Food Research International, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Development of a high-throughput LLE-UPLC-QqQ-MS/MS method and comprehensive profiling of urinary steroid hormones in Chinese elderly adults - Xiao Ma; Huimin Ren; Li Zhao; Xiaojie Guo; Jiran Zhang; Juan Liu; Xiaona Wang; Mengyao Wang; Yifu Lu; Shilu Tong; Hongyang Cui; Hong Chang; et al. (Analytica Chimica Acta, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

Flavor modulation of braised He Bao carp (Cyprinus carpio) by natural plant spices: Insights from GC–MS, GC–IMS, E-nose, E-tongue, and molecular docking analyses - Yuwei Liu; Yuting Wang; Ziyi Liu; Chang Li; Qiang Yu; Jianhua Xie; You Long; Qianzhu E; Yi Chen (Food Bioscience, 2026)

Immunological Characteristics of Triploid Grass Carp (Ctenopharyngodon idella) and evaluation of its phagocytosis in the macrophages of head kidney - Xiaoman Huang; Zixuan E; Hao Yang; Guihong Lai; Shuang Liu; Shujia Liao; Jiaqi Lin; Siyi Liu; Chen Long; Haoran Lin; Danqi Lu; Shuisheng Li; et al. (Fish & Shellfish Immunology, 2026)

Self-supplying glucose/oxygen hydrogel enhances dental pulp stem cell survival and vascularized tissue regeneration through Erk1/2-VEGF signaling - Xinyu Liu; Xiaofan Liu; Yuping Zhao; Yang Liu; Huimin Wang; Yi Li; Nan Ma; Hongchen Sun; Fermín E. González; Youliang Zhu; Junfeng Zhou; Yuewei Zhang; et al. (Chemical Engineering Journal, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Advancing high-resolution hourly PM2.5 forecasting with a hybrid framework integrating numerical simulation and machine learning - Yuan Liu; Zizheng Li; Pablo E. Saide; Ming Zhang; Qingqing He (Atmospheric Research, 2026)